Effect of a bacterial inoculum and additive on dry matter in situ degradability of sugarcane silage - José A Reyes-Gutiérrez; Oziel D Montañez-Valdez; Ramón Rodríguez-Macias; Mario Ruíz-López; Eduardo Salcedo-Pérez; Cándido E Guerra-Medina (Journal of Integrative Agriculture, 2015)
The objective of this study was to evaluate the effect of adding a bacterial inoculum and a handmade additive to sugarcane silage (SCS) on the in situ digestibility of dry matter (DM). The treatments were: T1) sugarcane silage (SCS) and T2) sugarcane silage with 1% inoculum and 1% additive (SCS+). The bacterial inoculum consisted of 10.0% molasses, 1.0% yogurt, 5.0% chicken manure, 0.5% urea, and 83.0% water, and the additive was formulated with 1.0% urea, 0.1% ammonium sulfate, and 0.25% phosphorus. In situ dry matter digestibility (DMD) was determined using the nylon bag technique with four cows equipped with ruminal fistulas. Cows were fed with ensiled sugarcane supplemented with 1 kg of commercial concentrate. 5 g of ground sample for each sugarcane treatment were weighted in nylon bags and incubated for 4, 8, 12, 24, 48, and 72 h in a completely randomized design with six replicates. The DMD (%) was higher (P<0.05) for SCS+ for all incubation times when compared with SCS. There were no differences in ruminal pH between the treatments for all the incubation times. The data suggested that the sugarcane silage with bacterial inoculum and additive could be an alternative for providing forage for ruminants during the season of low growth and quality grass.